La columna periodística: de esos embusteros días del ego inmarchitable. - Casals Carro, María Jesús (Estudios sobre el Mensaje Periodístico, 2000)
The column is the opinion journalistic genre in which for many reasons the ego of the writer is more clearly shown: because of his regular appointment with the readers, his historical and literary roots and the analysis and revelations that are required of him. In any case, the journalist column is the container of many and varied egos. The column mission 31 María Jesús Casals Carro La columna periodística: de esos embusteros días del ego unmarchitable to inform, to guide, to entertain, to delight, to convince, to persuade and to be in possession of the truth is as exhausting as pretending to keep young for ever. The columnist is not a liar. But he is convinced of being unwitherible, he believes his opinion is the best one. The columnists are ageless, writers of the ego, conjurers of ideas and words. Yesterday and Today. For tomorrow, only some warnings dedicated to the future columnists: they should prepare their ego and should cultivate the excellence. It is an arduous task but has an unquestionable social benefit.